Web-based Interactive Distance Learning Design with Moodle - Aspia Manurung, Asrar; Syafrayani, Putri Rizki (Aksaqila International Humanities and Social Sciences [AIHSS] Journal, 2024)
The rapid development of technology is driving integration towards education. Web-based interactive distance learning is one of the proofs of the improvement of technology. The current research provides the design of how web-based interactive distance learning by using Moodle through a systematic literature review. The data was taken from searches databases and then found out 9 articles regarding the Moodle learning system. It was found that Moodle provides many features that can enhance the learning process, as well as facilitate the learning environment regardless of place and time. However, the shortcomings were also found that it can be less satisfying because of the cost and the communication that existed in the Moodle also affected the satisfaction of the learning system. A deep considerable is needed by the educational practioners regarding the utilisation of Moodle in learning system.